2017
DOI: 10.3389/fnhum.2017.00155
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Increase in Corticomuscular Coherence during Bilateral, Cyclical Ankle Movements

Abstract: In humans, the midline primary motor cortex is active during walking. However, the exact role of such cortical participation is unknown. To delineate the role of the primary motor cortex in walking, we examined whether the primary motor cortex would activate leg muscles during movements that retained specific requirements of walking (i.e., locomotive actions). We recorded electroencephalographic and electromyographic signals from 15 healthy, young men while they sat and performed bilateral, cyclical ankle move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
4
20
0
Order By: Relevance
“…This is possibly due to the fact, that these studies tested muscle functions and therefore estimated CMC during isolated movements, whereas all muscles involved and examined during BpS likely share a common executive blueprint and act collectively to achieve the BpS. There is evidence to support this assumption, for example, Yoshida, et al 43 examined CMC during cyclical ankle movements and were able to observe beta range CMC in both m. tibialis anterior and m. gastrocnemius, serving as agonist and antagonist. Additionally, CMC between agonist-antagonist muscle pairs was also present in the beta range for elbow flexions in healthy adults 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is possibly due to the fact, that these studies tested muscle functions and therefore estimated CMC during isolated movements, whereas all muscles involved and examined during BpS likely share a common executive blueprint and act collectively to achieve the BpS. There is evidence to support this assumption, for example, Yoshida, et al 43 examined CMC during cyclical ankle movements and were able to observe beta range CMC in both m. tibialis anterior and m. gastrocnemius, serving as agonist and antagonist. Additionally, CMC between agonist-antagonist muscle pairs was also present in the beta range for elbow flexions in healthy adults 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Coherence was estimated in beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) and high gamma (44-60 Hz) frequency bands, across all muscles (8) and periods (3), resulting in 24 variables of interest for each frequency band.…”
Section: Corticomuscular Coherence During Bps (Cmc)mentioning
confidence: 99%
“…If CMC reflects the descending drive to the muscle, one would expect to find CMC at different phases of the gait cycle for different leg muscles. However, it is worthwhile noting that during dynamic ankle movements beta CMC has been observed during dorsiflexion for two antagonistic muscles (Yoshida et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further experimental investigation of CMC between cortex and leg muscles other than the TA during walking would help to resolve the timing of intra-stride modulations of CMC, as one would expect to find CMC at different phases of the gait cycle. However, it is worthwhile noting that during dynamic ankle movements beta CMC has been observed during dorsiflexion for two antagonistic muscles (Yoshida et al 2017). The case-reports by Winslow et al (2016) and Brantley et al (2016) investigated CMC during overground walking in a single subject over a single gait cycle: Winslow et al (2016) observed CMC between motor cortex and TA at approximately 18-23 Hz just after heel strike and just after toe-off, whereas Brantley et al (2016) reported CMC between motor cortex and TA at frequencies below 5 Hz throughout the gait cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the CMC was calculated from 0 to 1 bounded corticomuscular values as the volume under the time‐frequency map of magnitude‐squared coherence only where the wavelet cross‐spectrum between the EEG and EMG signals was detected as significant (Charissou et al ., ; Yoshida et al ., ). Over the [+3 + 6] s period of interest, the magnitude of the CMC was computed in two frequency bands of interest: [8–13] Hz (CMC 8‐13 ) (Christou et al ., ) and [13–31] Hz (CMC 13‐31 ) (Mima et al ., ).…”
Section: Methodsmentioning
confidence: 99%